Autenticitatea și simulacrele ei în noile contexte culturale, politice și economice - Ștefan Firică (Revista de Istorie și Teorie Literară)
After Theodor Adorno’s rebuff of authenticity in 1964, theories of identity underwent major changes in the attempt to address the new challenges of the economic, political, and cultural environments. This article is intended to take a look into three discourses on identity, showcasing a shift of perspective in the American cultural studies of the 1970s, 2000s, and 2010s. Lionel Trilling’s mostly culturalist approach, in the 1970s, gave rise to critics coming from intellectuals affiliated to the whole political spectrum, from the neo-con to the New Left. Charles Guignon transferred the concept of identity from the “high” territories of elite culture to the “lower” field of pop-culture, from self-help literature and media to punk rock and heavy metal. Somogy Varga followed its trace from the first self-help manual (in mid-19th c.) to the consumerism and counter-culture of the latest decades. The new paradigm of business management, starting at the beginning of the 1990s, relies on such notions as self-marketing, self-management or personal branding. In this new capitalist environment, authenticity has become a competitive advantage on the global market, but, letting itself go with the flow of production, it has lost its counter-cultural impetus and, rather often than not, turned into its opposite, inauthenticity. Today, the potential of political critique associated to the concept seems, therefore, endangered.